Familial Mediterranean Fever Triggered by Menstruation – A Case Report from Zambia - Maksoud, Gamal; Nyirenda , Christopher (Clinical Medicine And Health Research Journal, 2024)
Familial Mediterranean Fever (FMF) is an autoinflammatory autosomal-recessive disorder that is characterized by recurrent attacks of abdominal pains, fevers and serositis. It is highly prevalent among people from the Mediterranean basin including Arabs and Turks. However, due to the increase in migration worldwide, we start to recognize cases of FMF outside the Mediterranean region. We present the case of a 27-year-old Lebanese female residing in Zambia whose recurrent attacks constantly coincided with her menstruation. Due to the rarity of occurrence of FMF in regions such as Zambia, the coming up with the diagnosis was delayed and unnecessary interventions such as exploratory laparotomy were done. This case aims to highlight the importance of considering FMF and its potential triggers especially menstruation by the healthcare providers in non-Mediterranean areas to ensure timely recognition and management to avoid serious future complications such as amyloidosis.